Pengaruh Kepemimpinan Transformasional Kepala Sekolah dan Iklim Organisasi Sekolah Terhadap Disiplin Kerja Guru TK Se-Kecamatan Ungaran Barat Kabupaten Semarang - Novita Sari, Puput (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
The aims of this research are (1) to determine the magnitude of the influence of the school principal's transformational leadership style on the work discipline of kindergarten teachers, (2) to determine the magnitude of the influence of the school organizational climate on the work discipline of kindergarten teachers, (3) to determine the magnitude of the influence of the school principal's transformational leadership style and the school organizational climate together on the work discipline of kindergarten teachers in West Ungaran District, Semarang Regency. The research used a quantitative approach, from a population of 153 school principals and kindergarten teachers in East Ungaran District, Semarang Regency, a sample of 110 respondents was selected using proportional random sampling techniques. The data analysis used was descriptive analysis, classical assumption testing and regression testing using SPSS for Windows Release 26. The results of the research (1) there is a positive influence of the principal's transformational leadership style on teacher work discipline with a contribution of 0.672 or 67.2%, (2) there is a positive influence of organizational climate on work discipline with a contribution of 0.585 or 58.5%, (3) ) there is a positive influence of the principal's transformational leadership style and the school's organizational climate together on teacher work discipline with a contribution of 0.703 or 70.3%.